Exploration of Science Learning Strategies for Blind Students at the Sejahtera State Elementary School in Bogor City - Qisthi, Annisa; Yektyastuti, Resti; Hamami, Fauziyatul; Erlangga, Sony Yunior (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
The education or teaching needed by children with special needs or blindness is different from normal children. As should get more attention, special education and teaching. Because they have the same educational nature and religious potential as normal students. This study aims to 1) Find out what learning strategies can be applied to involve blind students in science learning. 2) Find out what challenges are faced in science learning for blind students. The research method used is qualitative phenomenology, with data collection techniques including interviews, observations, and documentation. Data were analyzed with thematic data analysis. To test the validity of the data using member check. The results of this study indicate that one of the important learning strategies is learning media, the media is in the form of audiovisual and 3-dimensional objects that can be touched by blind students, while the challenges faced in science learning for blind students are the lack of facilities and infrastructure in the form of learning media. The conclusions of this study are: 1) Science learning strategies for blind students are school policies, learning outside the classroom, then teacher abilities, and student mobility orientation. 2) The challenges faced in science learning for blind students are challenges in the classroom, characteristics of blind students, cognitive abilities, and facilities and infrastructure.